Identification of ATP2C1 mutations in the patients of Hailey-Hailey disease - Xiaoli Li; Dingwei Zhang; Jiahui Ding; Li Li; Zhenghui Wang (BMC Medical Genetics, 2020)
Abstract Background Familial benign chronic pemphigus, also known as Hailey-Hailey disease (HHD), is a clinically rare bullous Dermatosis. However the mechanism has not been clarified. The study aim to detect novel mutations in exons of ATP2C1 gene in HHD patients; to explore the possible mechnism of HHD pathogenesis by examining the expression profile of hSPCA1, miR-203, p63, Notch1 and HKII proteins in the skin lesions of HHD patients. Methods Genomic DNA was extracted from peripheral blood of HHD patients. All exons of ATP2C1 gene in HHD patients were amplified by PCR and the products were purified and sequenced. All related signaling proteins of interest were stained by using skin lesion tissues from HHD patients and miR-203 levels were also determined. Results One synonymous mutation c.G2598A (in exon 26), one nonsense mutation c.C635A and two missense mutations c.C1286A (p.A429D) and c. A1931G (p. D644G) were identified. The nonsense mutation changed codon UCG to stop codon UAG, causing a premature polypeptide chain of the functional region A. The two missense mutations were located in the region P (phosphorylation region) and the Mn binding site of hSPCA1. The level of hSPCA1 was significantly decreased in HHD patients compared to the normal human controls, accompanied by an increase of miR-203 level and a decrease of p63 and HKII levels. Conclusion In our study, we found four mutations in HHD. Meanwhile we found increase of miR-203 level and a decrease of p63 and HKII levels. In addition, Notch1, which was negatively regulated p63, is downregulated. These factors may be involved in the signaling pathways of HHD pathogenesis. Our data showed that both p63 and miR-203 may have significant regulatory effects on Notch1 in the skin.